Adoption factors of P3 sweetener towards achieving consumer satisfaction - Hasim, Mohamad Aidil (2020)
Recent innovations in nanotechnology have transformed the scientific and industrial fields including the food industry and it took a number of forms. These include applications of nanotechnology in food processing, food safety, food packaging, food materials, and in the foods itself. Nanotechnology in food is also known as nanofood. P3 Sweetener is one instance of a nanofood product in Malaysia, which can enhance taste, nutritional value, food quality, and shelf life of the product. However, consumers’ knowledge and understanding are still limited towards nanofood product due to resistance in technology and unfamiliarity of the context utilised. Thus, this research was carried out to identify the adoption factors affecting purchase behaviour towards consumer satisfaction. A survey was conducted and 365 answers were collected from P3 Sweetener users in Johor based upon purposive sampling plan (homogenous sampling) and this research was fully conducted quantitatively. The model was adapted from Stimulus Organism Response (SOR) and elicits four influencing factors which include knowledge, trust, perceived benefit and motivation. The findings of Exploratory Factor Analysis (EFA) has identified the four influencing factors as well structured in the scale. Based on the Multiple Regression Analysis (MRA), it has shown that trust, perceived benefit, and motivation have positive significant effects on purchase behaviour, and the most significant factor was motivation. However, knowledge was considered insignificant to purchase behaviour. Meanwhile, the finding of Hierarchical Regression Analysis (HRA) indicated that age has a moderating effect on the relationship between (knowledge and purchase behaviour) and (trust and purchase behaviour). Nevertheless, age was insignificant as a moderator for the relationships of (perceived benefit and purchase behaviour) and (motivation and purchase behaviour). Therefore, this research managed to produce a model that has an impact on the research contribution. As a result of this research, practitioners are able to understand the needs of their consumers in order to plan their marketing more strategically. Last but not least, it helps to enhance consumers understanding towards purchase behaviour of nanofood.